Encounters between Jesuits and Protestants in Africa - Maryks, Robert A.; Mkenda, Festo, 1968- (Jesuit Studies - Modernity through the prism of Jesuit history, 2018)
Protestants entering Africa in the nineteenth century sought to learn from earlier Jesuit presence in Ethiopia and southern Africa. The nineteenth century was itself a century of missionary scramble for Africa during which the Jesuits encountered their Protestant counterparts as both sought to evangelize the African native. Encounters between Jesuits and Protestants in Africa, edited by Robert Alexander Maryks and Festo Mkenda, S.J., presents critical reflections on the nature of those encounters in southern Africa and in Ethiopia, Madagascar, the Democratic Republic of Congo, and Fernando Po. Though largely marked by mutual suspicion and outright competition, the encounters also reveal personal appreciations and support across denominational boundaries and thus manifest salient lessons for ecumenical encounters even in our own time. This volume is the result of the second Boston College International Symposium on Jesuit Studies held at the Jesuit Historical Institute in Africa (Nairobi, Kenya) in 2016. Thanks to generous support of the Institute for Advanced Jesuit Studies at Boston College, it is available in Open Access.